Rabbit & robot the sleepover - Bell, Cece (Somerville, Mass Candlewick, 2012)
Rabbit is excited about the sleepover he has carefully planned for his friend Robot, but Robot has some different ideas about how things should go
"A Junior Library Guild selection"--Jkt. flap
Keywords: Friendship -- Fiction; Humorous stories; Rabbits -- Fiction; Robots -- Fiction; Sleepovers -- Fiction; JUVENILE FICTION / General; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Social Issues / Friendship